The Use of Popular Social Media On Guidance And Counseling Services In Middle School Counselors - Kheren Carollina Pamintarso; Adi Atmoko; Henny Indreswari; Joice Zhenrike Memmase; Irene Maya Simon (Department of Guidance and Counseling, FIP, Undiksha, 2022)
Along with technological developments, social media applications have emerged that support the dissemination of content, either in the form of photos or videos, guidance and counseling in schools needs to take advantage of its existence as a friendly and attractive BK service media for students. TikTok and Instagram are the most popular social media among teenagers that can be used as a medium for guidance and counseling services. This quantitative research on counselors or guidance and counseling teachers in East Java aims to capture the most popular use of social media among students. The results of this study describe the opinions of counselors or guidance and counseling teachers regarding the development and use of guidance and counseling media during the pandemic and how to use social media in counseling services. The results of the study became preliminary research in improving the competence of counselors in developing social media for guidance and counseling.